Low temperature deposition of 2D WS2 layers from WF6 and H2S precursors: impact of reducing agents. Issue 86 (14th September 2015) - Delabie, A.; Caymax, M.; Groven, B.; Heyne, M.; Haesevoets, K.; Meersschaut, J.; Nuytten, T.; Bender, H.; Conard, T.; Verdonck, P.; Van Elshocht, S.; De Gendt, S.; et al.
Abstract : We demonstrate the impact of reducing agents for Chemical Vapor Deposition (CVD) and Atomic Layer Deposition (ALD) of WS2 from WF6 and H2 S precursors. Abstract : We demonstrate the impact of reducing agents for Chemical Vapor Deposition (CVD) and Atomic Layer Deposition (ALD) of WS2 from WF6 and H2 S precursors. Nanocrystalline WS2 layers with a two-dimensional structure can be obtained at low deposition temperatures (300–450 °C) without using a template or anneal.